2020
DOI: 10.1111/apt.15808
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic thresholds for golimumab serum concentrations during induction and maintenance therapy in ulcerative colitis: results from the GO‐LEVEL study

Abstract: SummaryBackgroundSignificant associations between serum golimumab concentrations and favourable outcomes have been observed during both induction and maintenance therapy in ulcerative colitis (UC). However, data regarding optimal therapeutic serum golimumab concentration thresholds are limited.AimsTo identify optimal serum golimumab concentration thresholds during induction and maintenance treatment with golimumab.MethodsGO‐LEVEL was an open label, phase IV study that included a prospective cohort of UC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…The PANTS study, where anti-TNF naïve patients with luminal CD were enrolled at the time of anti-TNF initiation and prospectively observed until treatment discontinuation, reported that low TLs of infliximab (<7 mg/L) or adalimumab (<12 mg/L) at week 14 correlated with primary non-response at week 14 (odds ratio [OR] 0.35, 95% confidence interval [CI] 0.20-0.62, p = 0.00038 for infliximab; OR 0.13, 95% CI 0.06-0.28, p < 0.0001 for adalimumab) and non-remission at week 54 (OR 0.29, 95% CI 0.16-0.52, p < 0.0001 for infliximab; OR 0.03, 95% CI 0.10-0.12, p < 0.0001 for adalimumab) [87]. Similar associations between TLs and therapeutic outcomes have also been observed for golimumab, both in the post-hoc analysis of the registration trial [88] and in some observational studies [89][90][91][92]. Some studies have suggested that specific disease phenotypes might need higher TLs to be adequately controlled.…”
Section: Therapeutic Drug Monitoringsupporting
confidence: 62%
“…The PANTS study, where anti-TNF naïve patients with luminal CD were enrolled at the time of anti-TNF initiation and prospectively observed until treatment discontinuation, reported that low TLs of infliximab (<7 mg/L) or adalimumab (<12 mg/L) at week 14 correlated with primary non-response at week 14 (odds ratio [OR] 0.35, 95% confidence interval [CI] 0.20-0.62, p = 0.00038 for infliximab; OR 0.13, 95% CI 0.06-0.28, p < 0.0001 for adalimumab) and non-remission at week 54 (OR 0.29, 95% CI 0.16-0.52, p < 0.0001 for infliximab; OR 0.03, 95% CI 0.10-0.12, p < 0.0001 for adalimumab) [87]. Similar associations between TLs and therapeutic outcomes have also been observed for golimumab, both in the post-hoc analysis of the registration trial [88] and in some observational studies [89][90][91][92]. Some studies have suggested that specific disease phenotypes might need higher TLs to be adequately controlled.…”
Section: Therapeutic Drug Monitoringsupporting
confidence: 62%
“…Golimumab is also available in vials for infusion for very specific indications such as rheumatoid arthritis, active psoriatic arthritis, active ankylosing spondylitis, and active polyarticular juvenile idiopathic arthritis [ 14 ] Furthermore, clinical studies do not support the recommendation to treat low-weight children with 115/60 mg of golimumab. The GO-LEVEL study proposed using therapeutic drug monitoring to optimize golimumab dosing, with therapeutic thresholds of 3.8 g/mL at week 6 and 2.4 g/mL during maintenance [ 15 ]. This is also impractical, as these tests do not exist in many developing countries, including Syria.…”
Section: Discussionmentioning
confidence: 99%
“…35 The evidence at the time was too sparse to recommend a cutoff for golimumab, although subsequent studies have reinforced a therapeutic level of 2.4 to 3.2 mg/mL during maintenance treatment. [36][37][38] These guidelines highlighted the many difficulties with recommending therapeutic cutoffs for biologics, as acknowledged by the authors and as further discussed below.…”
Section: Anti-tumor Necrosis Factormentioning
confidence: 99%